Evaluación de índices eutomológicos mediante herramientas electrónicas en Villavicencio, Meta, Colombia (2023)
Objective: Determine the effectiveness of two electronic tools for the evaluation of aedic indices in the city of Villavicencio. Methods: An observational analytic study was conducted in two districts in the city of Villavicencio: Quintas de San Fernando and Cedritos. The form designed by the Ministry of Health to evaluate aedic indices was digitalized into two electronic media. Efficacy was determined on the basis of effective data collected and delivery time. An estimation was made of aedic indices. Breteau. household and pupae. A survey was conducted to determine attitudes to arbovirus infections. Use was made of descriptive statistics, chi-squared tests and Student’s t-test (r < 0.05).Results: Sixty-seven households were evaluated in two districts. The effective data index was better in areas where access to the Internet was permanent (100 % xu023.9 %). Delivery time was also affected by Internet connection. Significant differences were found between the two districts in the number of positive households for Cgf gu”cgi {rvk(r= 0.0052). as well as in the number of positive ground water tanks (r= 0.0123). Of the respondents. 16.4 % (95% CI. 8.9%-27.5 %) were aware that transmission had been by the bite of CgO’cgi {rvk mosquitoes. For 79.1 % each family was responsible for eliminating the breeding sites. Conclusions: Use of electronic tools speeds up the flow of information and creates an effective, easily-accessible and safe system which could be permanently implemented for entomological and public health surveillance. © 2019, Editorial Ciencias Medicas. All rights reserved.